Cobertura periodística deportiva, análisis comparativo de género - Farro Acosta, Reynaldo Andrés (2024)
Journalistic coverage has gone around the world, this is where sport in its different variables has taken off, people can stay out of the local, national and international events through the different broadcasts that are generated day after day in In relation to the athletic issue, however, is where the problem on which the research focuses appears. Covering events is one of the needs that the media has worldwide, but this arouses the curiosity of wanting to know, which gender is the most present when reporting certain events, that is, there is more intervention by women Or it is men who predominate this circumstance, if so, the main causes are sought and in this way ideas are proposed in order to generate equality between the two sexes (male and female). The persons interviewed details that the media tend to provide similar coverage spaces for both genders, only that the environment that the journalist must go to regardless of their gender, is not the same, the situations for each one are different, that is which raises the doubt that if an imbalance is generated in the aspect detailed previously.